Advances in ginsenoside treatment for common kidney diseases: pharmacological evaluation and potential mechanisms - Jin, Tonghui; Du, Yu; Liu, Chaoyue; Zhao, Jingming; Liu, Tiejun (Frontiers in Pharmacology, 2025)
Common kidney diseases include acute kidney injury, diabetic kidney disease, kidney cancer, and other related conditions. Ginsenosides, the principal bioactive constituents of ginseng, have been widely reported as therapeutic agents against these disorders. However, recent advances regarding their efficacy in kidney diseases have not been comprehensively synthesized. This review addresses this gap by summarizing current findings on the mechanisms and therapeutic targets of ginsenosides. Literature from PubMed, Web of Science, and other databases was systematically retrieved using keywords such as ginsenosides, acute kidney injury, diabetic nephropathy, renal cell carcinoma, lupus nephritis, and aging-related kidney injury. Evidence from cell-based and animal studies demonstrates that ginsenoside compound K, Rg1, Rg3, Rh2, Rb1, Rb3, Rg2, and Rg5 are the most frequently reported for kidney protection. Mechanistically, ginsenosides modulate multiple signalling networks, including NF-κB, PI3K/AKT, MAPK, TGF-β/Smads, PPAR, SIRT1, NLRP3, and Nrf2, to mitigate inflammation, oxidative stress, apoptosis, epithelial-mesenchymal transition, pyroptosis, autophagy, and endoplasmic reticulum stress. Taken together, these findings provide valuable insights into the therapeutic potential of ginsenosides and underscore their promise as candidates for the prevention and treatment of kidney diseases.